Inulin supplementation induces expression of hypothalamic antioxidant defence genes in weaned piglets. Issue 1 (7th March 2022) - Yang, Can; Lu, Hang; Li, Enkai; Oladele, Paul; Ajuwon, Kolapo M.
Abstract: Fibre plays an important role in diluting dietary energy density. Fibre is also implicated in the regulation of appetite, perhaps through direct effects in the brain. However, there is little information on this effect in pigs. Therefore, this study was conducted to investigate the effect of fibre type in regulating the expression of genes involved in appetite control, inflammation and antioxidant defence in the hypothalamus of weaned piglets. A total of 64 Duroc × Landrace × Yorkshire barrows at 37 days old were blocked by body weight and allotted to two dietary treatments, supplementation with either 0.25% cellulose (Solka‐Floc) or inulin (INU) for 28 days, after which animals were killed for analysis. Pigs fed INU had a tendency ( p  = 0.06) for reduced feed intake in the first week, although this effect disappeared in subsequent weeks. Pigs supplemented with INU had lower expression of dopamine (dopamine receptor D2), serotonin (5‐hydroxytryptamine receptor 1B), free fatty acid (GPR43) and neuropeptide Y receptor Y2 receptors in the hypothalamus ( p  < 0.05). Expression of the tryptophan hydroxylase 2 gene in the hypothalamus also tended ( p  = 0.09) to be lower for pigs fed INU. The abundance of antioxidant defence genes, superoxide dismutase ( SOD1 ) and catalase, were greater ( p  < 0.05) but that of a proinflammatory gene, interleukin 1β, was lower ( p  < 0.05) in the hypothalamus of pigs fed INU. Therefore, consumption of INU causes downregulation of inflammation in the hypothalamus and regulation of the abundance of serotonin or dopamine receptors, and may also increase antioxidant defence through upregulation of SOD and catalase in weaned piglets.